Psychological Capital, College Adaptation, and Internet Addiction: An Analysis Based on Moderated Mediation Model - Bi, Xiangyang; Jin, Jun (Frontiers in Psychiatry, 2021)
Using data from a baseline survey of college students, this study examined the possible mechanism by which psychological capital influences college students’ internet addiction through the mediation effect of their individual college adaptability. The study constructed a parallel multiple mediation effect model to help understand the effect mechanisms among these factors. The results indicated that psychological capital had a triple effect on internet addiction: (1) Psychological capital had a direct effect of helping reduce college students’ internet addiction; (2) emotional, learning, and interpersonal adaptation not only reduced internet addiction directly but also played mediating roles in the relationship between psychological capital and internet addiction; and (3) the mediation effects of emotional and interpersonal adaptation were moderated by psychological capital, leading to two different modes of mediation effects. As a whole, Psychological capital imposes a quadratic effect on internet addiction. The campus policy implications of these findings are discussed.